Erratum: Naive, M.A.K., Calimbo, L.G.L., Cudal, M.G., Alejandro, G.J.D. & Yu, W.B. (2022) Taxonomy of the genus Begonia (Begoniaceae) in Mindanao, Philippines IV: Begonia bangsamoro subsp. bagasa (Begoniaceae section Petermannia), a new subspecies from Zamboanga del Sur. Phytotaxa 559 (1): 88–94. - Naive, Mark Arcebal K.; Calimbo, Liberty Grace L.; Cudal, Maricris G.; Alejandro, Grecebio Jonathan D.; Yu, Wen-Bin (Phytotaxa, 2023)
N/A